PENGARUH MODAL KERJA, PENDIDIKAN DAN TEKNOLOGI TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI SENTRA INDUSTRI TAS DAN KOPER TANGGULANGIN - Noviono, Hadi; Pelitawati, Dyah (Jurnal Dinamika Administrasi Bisnis, 2019)
The purpose of this study is to determine the effect of work modalitis, education and technology on the income of Micro, Small, Medium Enterprises (MSME) in the Tanggulangin bag and luggage industry center. This study used quantitative research by looking at the amount of work modalities, the education level of the MSME owners, and the technology they use, used 73 samples of respondents in the Tanggulangin bag and luggage industry center with a simple random sampling method. The data analysis techniques used is multiple linear regression analysis. On this research, it was found that work modalities and education level had no effect on income partially, while technology had a negative effect on income partially at MSMEs in the Tanggulangin bag and luggage industry center. Simultaneously work modalities, education and technology have a significant influence on MSME income in the Tanggulangin bag and luggage industryKeywords : Work Modalities, Education, Technology, Income